The Walisongo's Abangan and Putihan Da'wah Methods in the Land of Java: Comparative Study of the Da'wah Methods of Sunan Kalijaga and Sunan Giri - Alfaruq, M Syaifuddin; Rozaq, Abdul (Jurnal Educatio FKIP UNMA, 2025)
The beginning of the spread of Islam in the archipelago began in the 11th century in the Malacca Peninsula area spread by merchants from the Middle East. While Islam began to settle in Java in the 14th century along with the collapse of the Majapahit Kingdom. The method used in this research is the Qualitative method, using a descriptive approach. The data collection method used by researchers is the interview method and Library Research. The specific research is on the dualism of the Walisongo da'wah flow, especially on the Abangan method used by Sunan Kalijaga and the Putihan method used by Sunan Giri. The method of da'wah used by Sunan Kalijaga and Sunan Giri was because the Javanese people had embraced the belief before Islam set foot in Java, this belief was called Kejawen or Kapitayan. The process of spreading Islam took place peacefully without any violence. The result of this dualism is the division of Muslims in Java, known as Abangan Islam and Putihan Islam. The Abangan Islam tends to worship using art, for example by using Javanese gending or songs, while the Putihan Islam worship based on the Qur'an and Hadith kaffah (perfect), they consider worshiping using art is a shirk.